Protective effects of citrus based mixture drinks (CBMDs) on oxidative stress and restraint stress - Cho, MyoungLae; Kim, Dan-Bi; Shin, Gi-Hae; Kim, Jae-Min; Seo, Yoonhee; Choe, Soo Young; Cho, Ju Hyun; Kim, Young-Cheul; Lee, Jin-Ha; Lee, Ok-Hwan (Food science and biotechnology, 2018)
In the current study investigated the protective effects of citrus based mixture drinks (CBMDs) using oxidative stress in human dermal fibroblast (HDF) cells and restraint-stressed rats. The CBMDs contained citrus bioflavonoids including narirutin and hesperidin. The cell viability of HDF cells treated with H 2 O 2 was observed at 53.9% but treated with CBMD-1 and CBMD-2 (500 μg/mL) on H 2 O 2 exposed HDF cells significantly increased the relative cell viability at 65.0 and 72.2%, respectively. In the treadmill test, the time spent on the electrode plate in the restraint-stressed group was analyzed 24.1 s, but restraint-stressed rats with administered CBMDs (300 mg/kg) had significantly decreased the time at 2.4 (CBMD-1) and 4.7 (CBMD-2) s, respectively. In addition, number of touches the electrode plate in restraint-stressed group was observed at 42.4 ea, but, restraint-stressed rats with administered CBMD-1 and CBMD-2 (300 mg/kg) were significantly decreased at 7.0 and 10.2 ea, respectively.